2013
DOI: 10.1105/tpc.113.116582
|View full text |Cite
|
Sign up to set email alerts
|

Phosphatidylinositol 4,5-Bisphosphate Influences PIN Polarization by Controlling Clathrin-Mediated Membrane Trafficking inArabidopsis   

Abstract: The functions of the minor phospholipid phosphatidylinositol-4,5-bisphosphate [PtdIns(4,5)P 2 ] during vegetative plant growth remain obscure. Here, we targeted two related phosphatidylinositol 4-phosphate 5-kinases (PI4P 5-kinases) PIP5K1 and PIP5K2, which are expressed ubiquitously in Arabidopsis thaliana. A pip5k1 pip5k2 double mutant with reduced PtdIns(4,5)P 2 levels showed dwarf stature and phenotypes suggesting defects in auxin distribution. The roots of the pip5k1 pip5k2 double mutant had normal auxin … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
194
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 153 publications
(206 citation statements)
references
References 61 publications
12
194
0
Order By: Relevance
“…This interpretation also matches the previous observations that auxin efflux carrier abundance is reduced in the meristems of brx mutants (Scacchi et al, 2010) and that brx seedlings contain more free auxin per fresh weight (Sankar et al, 2011). It is also consistent with the proposed influence of the PIP to PIP 2 ratio on auxin efflux carrier polarization and plasma membrane abundance (Ischebeck et al, 2014;Tejos et al, 2014). It thus appears possible that locally disturbed polar auxin transport interferes with protophloem sieve element differentiation.…”
Section: The Systemic Effects Of Impaired Protophloem Developmentsupporting
confidence: 80%
See 3 more Smart Citations
“…This interpretation also matches the previous observations that auxin efflux carrier abundance is reduced in the meristems of brx mutants (Scacchi et al, 2010) and that brx seedlings contain more free auxin per fresh weight (Sankar et al, 2011). It is also consistent with the proposed influence of the PIP to PIP 2 ratio on auxin efflux carrier polarization and plasma membrane abundance (Ischebeck et al, 2014;Tejos et al, 2014). It thus appears possible that locally disturbed polar auxin transport interferes with protophloem sieve element differentiation.…”
Section: The Systemic Effects Of Impaired Protophloem Developmentsupporting
confidence: 80%
“…Similar to 5-phosphatases, the PIP5K genes are a family for which developmental roles are only about to emerge. For example, recently it has been reported that pip5k1 pip5k2 double mutants display severely reduced root growth and interrupted foliar vasculature (Ischebeck et al, 2014;Tejos et al, 2014), similar to our transgenic CVP2 overexpression lines. It will therefore be interesting to determine whether protophloem differentiation is impaired in pip5k1 pip5k2 double mutants as well as in pip5k1 single mutants (which already display reduced primary root growth).…”
Section: Resultsmentioning
confidence: 67%
See 2 more Smart Citations
“…In fact, the physiological consequences of enhanced PI formation tend to be rather limited and highly specific, raising the question of how the specificity of PI functions is achieved (Heilmann and Heilmann, 2013). A key piece of information for understanding PI function is that these lipids do not display uniform distribution within membranes (Ischebeck et al, , 2011(Ischebeck et al, , 2013Kost et al, 1999;Kusano et al, 2008;Sousa et al, 2008;Tejos et al, 2014;van Leeuwen et al, 2007;Vermeer et al, 2009;Vincent et al, 2005). Instead, PIs are enriched in certain membrane domains, and it is likely that such microdomains play a part in mediating the specific effects of PIs (Fig.…”
Section: Pis and Membrane Microdomainsmentioning
confidence: 99%